THE USE AND VALUE OF A CHILD ASSESSMENT TOOL (CAT) IN SOCIAL WORK CHILD ASSESSMENTS - Andiswa Mlotshwa (Stellenbosch University, 2021)
The integration of child-friendly tools during child counselling facilitates effective communication and child participation. However, the use of child-friendly tools in generalist child counselling remains sparse. This paper presents social work students’ perceptions of using a child assessment tool (CAT). While the study adopted a mixed-method approach, this paper reports the findings drawn from the study's qualitative findings. Data collection included individual semi-structured interviews with purposively sampled fourth-level student social workers. The results indicated that using the CAT created a child-friendly environment that facilitated effective child communication and participation during assessments. Using the CAT addresses barriers to child participation during child assessment.